Cas Walker : Stories on His Life and Legend - Hodge, Joshua S. (Book collections on Project MUSE., 2019)
"In collaboration with Dr. Ernest Freeberg, Josh Hodge has collected, transcribed, and converted a sequence of oral interviews into a manuscript of stories on the famous, and infamous, Cas Walker (1902-1998)--politician, businessman, music producer, and Knoxville legend. Hodge spent the majority of the summer of 2017 interviewing notable Knoxvillians who knew or remembered Walker. With Freeberg, he also spent time digging through archived news stories and speaking with reporters who covered Walker. While it would be difficult to create a seamless biography of Walker and his colorful life, this collection of memories about him will guarantee that various strands of his checkered legacy will live on"--